2005
DOI: 10.1007/s11167-005-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Content of Free Formaldehyde in Urea-Formaldehyde Resins

Abstract: The possibility of decreasing the content of free formaldehyde in urea3formaldehyde resins by varying the pH and urea3formaldehyde ratio in various synthesis steps was examined. Urea3formaldehyde resins containing no free formaldehyde were prepared.Urea3formaldehyde resins (UFRs) are widely used binders. Their significant drawback is the toxicity caused by the presence of free formaldehyde (FA); its content depends on the preparation conditions [1].The influence of process parameters on the properties and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…At the beginning of the 1970s, extensive research was conducted to reduce formaldehyde emissions from wood-based panels. The introduction of several methods, to industrial practice, of reducing the content of free formaldehyde from about 100 mg per 100 g of board to less than 8 mg per 100 g of board was the result of these studies, and was accomplished by changing the method of synthesis or by the use of various modifiers [ 21 , 22 ], which are substances that chemically bind formaldehyde, e.g., amines (urea, ammonia, melamine, and dicyandiamide), polyamines, sodium sulphite, or tannins [ 23 ]. Due to the ongoing work aiming to reclassify formaldehyde, more and more stringent standards regarding the emission of formaldehyde, and the strengthening of environmental awareness, it should be expected that its content and emissions from wood-based products will be further reduced in the future.…”
Section: Toxicity Of Formaldehydementioning
confidence: 99%
“…At the beginning of the 1970s, extensive research was conducted to reduce formaldehyde emissions from wood-based panels. The introduction of several methods, to industrial practice, of reducing the content of free formaldehyde from about 100 mg per 100 g of board to less than 8 mg per 100 g of board was the result of these studies, and was accomplished by changing the method of synthesis or by the use of various modifiers [ 21 , 22 ], which are substances that chemically bind formaldehyde, e.g., amines (urea, ammonia, melamine, and dicyandiamide), polyamines, sodium sulphite, or tannins [ 23 ]. Due to the ongoing work aiming to reclassify formaldehyde, more and more stringent standards regarding the emission of formaldehyde, and the strengthening of environmental awareness, it should be expected that its content and emissions from wood-based products will be further reduced in the future.…”
Section: Toxicity Of Formaldehydementioning
confidence: 99%
“…There is a gelation of the polymer leading to the formation of network in the second stage. In the preparation of such pre-polymers, some of the formaldehyde still remains [4,5]. Because of the toxic nature of formaldehyde, this 'free formaldehyde' constitutes a serious hazard in the use of these pre-polymers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Maslosh et al 10 reported that the alkaline-acid process produces resins with lower content of free formaldehyde as compared with the acid-alkaline process.…”
Section: Introductionmentioning
confidence: 99%